The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4049/jimmunol.1001172
|View full text |Cite
|
Sign up to set email alerts
|

Alloantibodies Prevent the Induction of Transplantation Tolerance by Enhancing Alloreactive T Cell Priming

Abstract: Circulating alloantibodies in transplant recipients are often associated with increased Ab-mediated as well as cellular rejection. We tested the hypothesis that alloantibodies facilitate cellular rejection by functioning as opsonins to enhance T cell activation using a BALB/c to C57BL/6 heart or skin transplant model. Long-term heart and skin survival induced with anti-CD154 alone or in combination with donor-specific transfusion (DST), respectively, was abrogated by the presence of anti-Kd mAbs, and alloreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 43 publications
5
37
0
Order By: Relevance
“…Our studies build upon previous work by others demonstrating that costimulatory signal deliver by helper T cells, predominantly transmitted via the indirect pathway of allorecognition, are required for induction of high titer, isotype switched, IgG, alloantibody reactive to donor antigens (7,8,10,(30)(31)(32)(33)(34)(35)(36). Using an allosensitization model in which the prior administration of a single fully MHC disparate splenocyte dose provides sufficient high-titer alloantibody to reject allogeneic BM grafts even 1 year postpriming, we newly demonstrate that only a combination of a highly depletionary anti-CD20 mAb plus LTbR-Ig that reduces GC formation sufficiently eliminates alloantibody to permit donor BM rescue of lethally irradiated, T-and NK-depleted recipients ( Figure 5D).…”
Section: Discussionsupporting
confidence: 68%
“…Our studies build upon previous work by others demonstrating that costimulatory signal deliver by helper T cells, predominantly transmitted via the indirect pathway of allorecognition, are required for induction of high titer, isotype switched, IgG, alloantibody reactive to donor antigens (7,8,10,(30)(31)(32)(33)(34)(35)(36). Using an allosensitization model in which the prior administration of a single fully MHC disparate splenocyte dose provides sufficient high-titer alloantibody to reject allogeneic BM grafts even 1 year postpriming, we newly demonstrate that only a combination of a highly depletionary anti-CD20 mAb plus LTbR-Ig that reduces GC formation sufficiently eliminates alloantibody to permit donor BM rescue of lethally irradiated, T-and NK-depleted recipients ( Figure 5D).…”
Section: Discussionsupporting
confidence: 68%
“…Secondly, this model does not define the effects of CTLA4-Ig on memory T cells the way that an adoptive transfer model would. However, we consider the sensitization of B and T cells and the presence of low levels of circulating antibodies a strength of this model, as we have previously shown that DSA can promote antigen uptake through opsonization, enhance antigen-presenting cell (APC) activation, and alter the signals provided by APCs to memory T cells (8,56). Indeed, we observed that the efficacy of CTLA4-Ig was inferior in recipients that were more recently sensitized and harbored higher levels of DSA.…”
Section: Cd4mentioning
confidence: 99%
“…Memory T cells are also relatively resistant to cell death, which allows them to accumulate more rapidly and to higher numbers (7). Sensitized recipients harbor higher donor-specific T cell frequencies and circulating antibodies that can, in turn, promote more vigorous T cell responses in vivo (8,9). In humans, previous transplantation, pregnancy, or blood transfusion are the most clinically important sensitizing events that result in increased donor-specific antibody (10), and presumably donor-specific T cells that provide help to the B cells producing these antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, there have been reports of effectiveness of B cell-depleting agents, complement blocking agents, or proteasome inhibitors, which block plasma cell Ab production, in transplantation (48)(49)(50). It has been suggested that memory B cells and alloantibodies can actually enhance alloreactive T cell priming and prevent tolerance toward the graft in a CD154-independent manner (51,52). This is also consistent with studies showing that alloantibodies can activate endothelial cells and monocytes to produce proinflammatory cytokines that enhance graft rejection (53).…”
Section: Discussionmentioning
confidence: 99%